Redox-Active Molecules as Therapeutic Agents - Ana Sofia Fernandes (MDPI AG, 2022)
Oxidative stress and altered redox signaling have been described in a plethora of pathological conditions, such as inflammation, cardiovascular diseases, diabetes, cancer, and neurodegenerative disorders, among others [...]